PERAN KEPOLISIAN DALAM MENANGGULANGI PENGENDARA SEPEDA MOTOR OLEH ANAK MENURUT UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI WILAYAH HUKUM KOTA PEKANBARU - S, Kartika; A, Syaifullah Yophi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Used motorcycles ranging from the lower class to the upper class. The advent of the automatic type motorcycle is also a factor, the broader coverage of motorcycle users. The number of children who ride motorcycles increased, especially school children. They thought that riding a motorcycle to school is very efficient, not too late, more efficient, and ease in transportation.From the research, there are three main things that can be inferred. First, the role of the police in tackling motorcyclists by children in the jurisdiction of the city of Pekanbaru performed the role of pre-emptive, preventive and repressive. Second, the barriers faced by the police in tackling motorcyclists by children in the jurisdiction of the city of Pekanbaru comes from internal factors and external factors. Third, the police's efforts in tackling motorcyclists by children in the jurisdiction of the city of Pekanbaru is the traffic police work together with the schools and provide socialization and education. Advice Author, First, The traffic police unit should improve and maximize performance. Second, add to the traffic police personnel unit and expand its facilities. Third, the traffic police work together with the schools and provide socialization and education, parents to better supervise the children in their environment.Keywords: Role-Police - Motorists - Motorcycle – Children